Bolstering Immunity through Pattern Recognition Receptors: A Unique Approach to Control Tuberculosis - Pahari, Susanta; Kaur, Gurpreet; Aqdas, Mohammad; Negi, Shikha; Chatterjee, Deepyan; Bashir, Hilal; Singh, Sanpreet; Agrewala, Javed N. (Frontiers in Immunology, 2017)
The global control of tuberculosis (TB) presents a continuous health challenge to mankind. Despite having effective drugs, TB still has a devastating impact on human health. Contributing reasons include the emergence of drug-resistant strains of Mycobacterium tuberculosis (Mtb), the AIDS-pandemic and the absence of effective vaccines against the disease. Indeed, alternative and effective methods of TB treatment and control are urgently needed. One such approach may be to more effectively engage the immune system; particularly the frontline pattern recognition receptor (PRR) systems of the host, which sense Pathogen Associated Molecular Patterns (PAMPs) of Mtb. It is well known that 95% of individuals infected with Mtb in latent form remain healthy throughout their life. Therefore, we propose that clues can be found to control the remainder by successfully manipulating the innate immune mechanisms, particularly of nasal and mucosal cavities. This article highlights the importance of signaling through PRRs in restricting Mtb entry and subsequently preventing its infection. Further, we discuss whether this unique therapy employing PRRs in combination with drugs can help in reducing the dose and duration of current TB-regimen.